1983
DOI: 10.1002/pssa.2210790132
|View full text |Cite
|
Sign up to set email alerts
|

The Silver Iodide–Thallium Iodide Pseudo-Binary System

Abstract: A form of the T-x section of the equilibrium phase diagram for the system AgI-TI1 is proposed on the basis of thermal and X-ray diffraction data. Two room temperature stable intermediate phases AgTII, and AgT& are confirmed, and evidence is found for two other phases, stable a t higher temperatures. The electrical conductivity is determined principally by the fraction of AgI present; fast ion conduction occurred only when or-AgI was present.Une forme du section du diagramme de phases pour le systeme AgI-TlI es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
5
0
1
Order By: Relevance
“…Dithallium-triiodoargentat Tl,AgI, entspricht in der Zusammensetzung den Iodoargentaten K2AgI, [3], Rb,AgI,[4] und Cs,AgI, [5] bzw. dem Iodocuprat (1) Tl, CuI,[ 6 ] . In den Kristallstrukturen der Alkali-Iodoargentate sind Ag1,-Tetraeder iiber gemeinsame Ecken zu Ketten f, [AgI,,21,]…”
Section: Introductionunclassified
“…Dithallium-triiodoargentat Tl,AgI, entspricht in der Zusammensetzung den Iodoargentaten K2AgI, [3], Rb,AgI,[4] und Cs,AgI, [5] bzw. dem Iodocuprat (1) Tl, CuI,[ 6 ] . In den Kristallstrukturen der Alkali-Iodoargentate sind Ag1,-Tetraeder iiber gemeinsame Ecken zu Ketten f, [AgI,,21,]…”
Section: Introductionunclassified
“…[10]. Moreover, X-ray powder diffraction study of alloys of the AgI-TlI system with 80 and 90 mol.% AgI quenched after annealing at 570 K did not confirm the literature assumption [11] about the existence of the -phase in the temperature range of 478-633 K. Apparently, the specified alloys consisted of two-phase mixtures of AgI and AgTlI 2 .…”
Section: Introductionmentioning
confidence: 89%
“…The ternary Ag-Tl-I system was investigated by several authors [10][11][12], mainly with respect to the AgI-TlI section. According to the literature [10] this section includes two ternary compounds AgTl 2 I 3 and AgTlI 2 melting congruently at 600 K and incongruently by the peritectic reaction at 513 K, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we synthesized a simple crystal structure phase AgTlI 2 (space group I4/mcm; eight atoms in the primitive cell (PC)) and found that it exhibits an exceedingly low κ of 0.25 W/mK at room temperature. AgTlI 2 was synthesized 22 , 23 and found to be an electrical insulator 23 , while no measurement of κ has been reported in the literature. We performed single-crystal diffraction refinement and found a considerable negative part of the probability density function for Ag atoms, directly unearthing the strongly anharmonic nature of Ag atoms.…”
Section: Introductionmentioning
confidence: 99%